Critical view of safety in laparoscopic cholecystectomy: A prospective investigation from both cognitive and executive aspects - Jin, Yi; Liu, Runwen; Chen, Yonghua; Liu, Jie; Zhao, Ying; Wei, Ailin; Li, Yichuan; Li, Hai; Xu, Jun; Wang, Xin; Li, Ang (Frontiers in Surgery, 2022)
Abstract Background: The achievement rate of critical view of safety during laparoscopic cholecystectomy is much lower than expected. This original study aims to investigate and analyze factors associated with low critical view of safety achievement. Materials and Methods: We prospectively collected laparoscopic cholecystectomy videos performed from September 2, 2021, to September 19, 2021, in Sichuan Province, China. The artificial intelligence system, SurgSmart, analyzed videos under the necessary corrections undergone by expert surgeons. Also, we distributed questionnaires to surgeons and analyzed them along with surgical videos simultaneously. Results: We collected 169 laparoscopic cholecystectomy surgical videos undergone by 124 surgeons, among which 105 participants responded validly to the questionnaire. Excluding those who conducted the bail-out process directly, the overall critical view of safety achievement rates for non-inflammatory and inflammatory groups were 18.18% (18/99) and 9.84% (6/61), respectively. Although 80.95% (85/105) of the surgeons understood basic concept of critical view of safety, only 4.76% (5/105) of the respondents commanded all three criteria error-freely. Multivariate logistic regression results showed unconventional surgical workflow (OR:12.372, P<0.001), misunderstanding of the 2nd (OR: 8.917, P<0.05) and 3rd (OR:8.206, P<0.05) criterion of critical view of safety, and don’t mistake “fundus-first technique” as one criterion of critical view of safety (OR:0.123, P<0.01), were associated with lower and higher achievement of critical view of safety, respectively. Conclusions: The execution and cognition of critical view of safety are deficient, especially the latter one. Thus, increasing critical view of safety surgical awareness may effectively improve its achievement rate.